Orthodontic traction of impacted upper central incisors related to mesiodens - Machado, André Wilson; Maia, Luiz Guilherme Martins; Vianna, Alexandre Protásio; Gandini JÚnior, Luiz Gonzaga (Faculdade São Leopoldo Mandic, 2015)
Although maxillary central incisors impaction is not a high frequent clinical condition, it is responsible for some undesirable aspects of patients smile from esthetic and functional points of view. There are some etiologic factors associated to this dental disturbance but the scientific literature is consensual on determining the importance of the early diagnosis and proper intervention. This manuscript consists on the case report of a 10 years old boy with Class I malocclusion, who showed during the mixed dentition phase, impaction of maxillary central incisors related to deciduous teeth retention and due to the presence of 2 mesiodens. The treatment proposed involved the surgical removal of the mesiodens, bonding of orthodontic accessories to the impacted incisors crowns followed by orthodontic traction with a removable orthodontic appliance. Regardless the development stage of the dentition was not ideal for this intervention, once the diagnosis should have been done as earlier as possible, favorable esthetic and functional results were attained.

A impacção de incisivos centrais superiores é uma condição clínica que embora não seja muito frequente, é um fator desagradável do ponto de vista estético e funcional. Existem diversas causas dessa alteração e a literatura é consensual quanto à necessidade da realização do diagnóstico e da intervenção o mais precocemente possível. Este trabalho traz o relato de um caso clínico de um paciente com 10 anos de idade, na fase da dentição mista, com má oclusão de Classe I, impacção de incisivos centrais superiores associado à retenção prolongada dos decíduos e a presença de dois supra-numerários na linha média. A conduta proposta foi à remoção cirúrgica dos mesiodens, colagem de dispositivos ortodônticos nos incisivos centrais impactados e, tracionamento ortodôntico com aparelho removível. Desta forma, embora a época de tratamento não fosse a ideal, pois o diagnóstico deveria ter sido estabelecido o mais precocemente possível, alcançou-se um resultado estético e funcional favorável.
Tracionamento ortodôntico de incisivos centrais superiores impactados associados à presença de mesiodens
Keywords: Malocclusion; Orthodontics; Tooth impacted; Má oclusão; Ortodontia; impactado